Willow the Wednesday fairy - Meadows, Daisy (New York : Scholastic Inc., 2008)
Kirsty and Rachel agree to help when Jack Frost steals Willow the Wednesday Fairy's Fun Day Flag, which almost meets with disaster when it gets cut up for projects at the arts and crafts day fair.
Includes an excerpt from the author's "Thea the Thursday Fairy."
Series at head of title
RL2.
006-009.
730L
Accelerated Reader AR
Keywords: Frost, Jack -- (Fictitious character) -- Fiction; Fairies -- Fiction; Flags -- Fiction; Goblins -- Fiction; Fiction